ASPEK YURIDIS TERHADAP AKSI MASSA DALAM UPAYA PENYAMPAIAN PENDAPAT MENURUT UNDANG-UNDANG NOMOR 39 TAHUN 1999 TENTANG HAK ASASI MANUSIA - Ony Rosifany (Universitas 17 Agustus 1945 Samarinda, 2013)
The protests have led to a polemic between the officers / officials of the demonstrator, which is between the rule implementing human rights or protecting government policies that conflict with the interests of the community.Expression in public is the right of every citizen of Indonesia as a sovereign state. To limit the rights and obligations of every Indonesian citizen has been expressly stipulated in the Law on expression in public. It's just in a staged rallies often forget protesters rights and obligations to be performed, so that the occurrence of the violation and can be categorized as a legal act.The action of the police in providing security situation demonstrators (as stipulated in the guidelines and codes of conduct security police) prevent it from spreading to bigger problems in the form of material damage and loss of life.